Analysis of the causes of hospitalization in the Intensive Care Unit of the Regional Specialist Hospital in Lublin - Rudnicka-Drożak, Ewa; Rybojad, Beata; Jaworska, Iwona; Korecka, Renata; Aftyka, Anna (Polish Journal of Public Health, 2010)
Introduction. Intensive Care units are departments managed by anesthesiologists which admit patients in life-threatening situations due to various reasons. The aim of this study was to analyze the causes of hospitalization of patients in Intensive Care Units. Material and methods. The method used in the research was the analysis of medical records, and the research tool was a questionnaire survey developed for the purpose of this study. The research was carried out at the Department of Anesthesiology and Intensive Care Unit of the Cardinal Stefan Wyszynski Regional Hospital in Lublin from October 2006 to October 2007. The study included 126 patients out of whom 26 subjects were excluded because of incomplete medical records. Conclusion. The hospitalization at the intensive care unit ranged from 1-7 days. The main causes of hospitalization in this department are: respiratory failure, the state after a sudden cardiac arrest and multi-organ injuries. Significant differences were found between patients’ age and the cause of hospitalization: the casualties of traffic accidents were people circa 32 years old. Older patients with an average age of 63 were mostly people transferred from other departments. The women were most often hospitalized at ICU after being transferred from other departments and the men also as a result of a transfer from other departments and because of traffic accidents.